Iranian-Saudi relations in economic and security cooperation (1991-2001) - Amiri, Reza Ekhtiari (2012)
Despite economic and political problems between Iran and Saudi Arabia, they finally agreed to cooperate on oil price in 1998-9 and also signed a security cooperation pact in 2001, both of which were for the first time. In view of this, this thesis revolves around three questions: first; what economic factors led to cooperation between Iran and Saudi Arabia within OPEC? Second, how did political elites of Iran and Saudi Arabia play an important role in the economic cooperation of the two countries within OPEC?, And finally, what political-security factors besides economic cooperation had a role in the security cooperation between Iran and Saudi Arabia? In this study, a qualitative research method was used and since the study took Iranian-Saudi cooperation into consideration from an Iranian perspective, the primary data were mostly collected through semi-structure open-ended interviews with ten Iranian diplomats and senior officials who held office regarding Iran-Saudi matters in Iran’s Foreign Ministry during the period of the study. The protocol for data recording was the use of audio tape-recorder and the interviews were mainly conducted in the office of the informants. At the end, with regard to the historical nature of the study, the researcher used qualitative content analysis to analyze and then interpret the gathered data. The findings indicate that the domestic economic problems of Iran and Saudi Arabia, as the internal factor, and the decline of world oil price and its continuing downward spiral for almost two years, as the external factor, were the main reasons for the eventual economic cooperation between the two countries regarding oil within OPEC. The findings also show how the political elites of Iran and Saudi Arabia, including President Akbar Hashemi Rafsanjani (1989-1997), Seyyed Mohammad Khatami (1997-2004), and Saudi Crown Prince Abdullah Ibn Abdul Aziz played significant roles in this cooperation. They helped to pave the way for eventual cooperation by improving bilateral political relations, which had been strained during the 1980s, since without normalization and advancement of mutual relations the two countries were not able to cooperate on oil price and quota. Finally, the study illustrates that in addition to the factor of economic cooperation, the political and security factors of confidence building by Iranian leaders, which assured Saudi leaders that Iran was not a security threat to them, the presence of Crown Prince Abdullah in Saudi’s foreign policy arena, improvement of relations between Iran and the West, the common threat of Al-Qaeda and Taliban in the region, and reduction of Iran’s revolutionary zeal and thoughts alongside the absence of any military hostilities between Iran and neighboring Arab countries in the Persian Gulf region during the 1990s, had a crucial role in the eventual signing of the Iran and Saudi Arabia novel security agreement in 2001, which was regarded as the turning point in their mutual relations since 1979. In conclusion, the research contributed to economic and security matters in bilateral cooperation between Iran and Saudi Arabia. The research also showed that economic and political issues were strongly correlated in Iranian-Saudi cooperation and also the political elite played a very crucial role in the cooperation between the two countries. This study, likewise, provides strong support to the neo-functionalist theory and promotes a better theoretical understanding and knowledge of regional integration and cooperation.